Asthma transition from childhood into adulthood. Issue 3 (March 2017) - Fuchs, Oliver; Bahmer, Thomas; Rabe, Klaus F; von Mutius, Erika
Summary: Asthma is themost prevalent chronic respiratory disease both in children and adults and resembles a complex syndrome rather than a single disease. Different methods have been developed to better characterise distinct asthma phenotypes in childhood and adulthood. In studies of adults, most phenotyping relies on biomaterials from the lower airways; however, this information is missing in paediatric studies because of restricted accessibility. Few patients show symptoms throughout childhood, adolescence, and adulthood. Risk factors for this might be genetics, family history of asthma and atopy, infections early in life, allergic diseases, and lung function deficits. In turn, a large proportion of children with asthma lose their symptoms during school age and adolescence. This improved prognosis, which might also reflect a better treatment response, is associated with being male and with milder and less allergic disease. Importantly, whether clinical remission of symptoms equals the disappearance of underlying pathology is unknown. In fact, airway hyper-responsiveness and airway inflammation might remain despite the absence of overt symptoms. Additionally, a new-onset of asthma symptoms is apparent in adulthood, especially in women and in the case of impaired lung function. However, many patients do not remember childhood symptoms, which might reflect relapse rather than true initiation. Both relapse and adult-onset of asthma symptoms have been associated with allergic disease and sensitisation in addition to airway hyper-responsiveness. Thus, asthma symptoms beginning in adults might have originated in childhood. Equivocally, persistence into, relapse, and new-onset of symptoms in adulthood have all been related to active smoking. However, underlying mechanisms for the associations remain unclear, and future asthma research should therefore integrate standardised molecular approaches in identical ways in both paediatric and adult populations and in longitudinal studies.